Regulation of cardiac function during a cold pressor test in athletes and untrained subjects - Ifuku, H.; Moriyama, K.; Arai, K.; Shiraishi-Hichiwa, Y. (European Journal of Applied Physiology, 2007)
By using (dP/dt)/P of carotid artery pulse, a non-invasive index of cardiac contractility, we examined the regulatory mechanism of cardiac function during a cold pressor test in athletes and untrained subjects. Twenty-four healthy subjects (9 athletes, 8 untrained subjects, and 7 hyperreactors of 4 athletes and 3 untrained subjects with a rise of 15 mmHg or greater in systolic and/or diastolic blood pressure) underwent the cold pressor test according to Hines and Brown (Am Heart J 11:1-9, 1936): immersion of the right hand in 4°C water for 1 min. Although mean blood pressure increased during the cold stress in all the groups, cardiac function differed. In athletes, heart rate and cardiac contractility caused cardiac output to increase while total peripheral resistance (TPR) did not change. In untrained subjects, however, heart rate and cardiac contractility tended to decrease cardiac output and thus TPR increased. In hyperreactors, heart rate and cardiac contractility increased during cold stress, and also TPR increased. After the end of the test, heart rate and cardiac contractility decreased only in untrained group. The findings that during a cold pressor test heart rate and cardiac contractility are enhanced in athletes but depressed in untrained subjects indicate that the state of physical training influences cardiac sympathetic neural reactivity to cold stress, except for hyperreactors.